Measurement of azimuthal correlations of D mesons with charged particles in pp collisions at √s=7 TeV and p–Pb collisions at √sNN=5.02 TeV - Adam, Jaroslav; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; Oeschler, Helmut; et al. (The European physical journal. C, Particles and fields, 2017)
The azimuthal correlations of D mesons with charged particles were measured with the ALICE apparatus in pp collisions at s√=7 TeVs=7 TeV{\sqrt{s}}=7~TeV and p-Pb collisions at sNN−−−√=5.02 TeVsNN=5.02 TeV{\sqrt{{{s}}_{\scriptscriptstyle {NN}}}}=5.02~TeV at the Large Hadron Collider. D0D0D^{0}, D+D+{D^{+}}, and D∗+D∗+{D^{*+}} mesons and their charge conjugates with transverse momentum 3<pT<16 GeV/c3<pT<16 GeV/c3<{p}_{T}<16~GeV/c and rapidity in the nucleon-nucleon centre-of-mass system |ycms|<0.5|ycms|<0.5|y_cms|<0.5 (pp collisions) and −0.96<ycms<0.04−0.96<ycms<0.04-0.96<y_cms<0.04 (p-Pb collisions) were correlated to charged particles with pT>0.3 GeV/cpT>0.3 GeV/cp_{T}>0.3~GeV/c. The yield of charged particles in the correlation peak induced by the jet containing the D meson and the peak width are compatible within uncertainties in the two collision systems. The data are described within uncertainties by Monte-Carlo simulations based on PYTHIA, POWHEG, and EPOS 3 event generators.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
ALICE Collaboration: J. Adam, V. Anguelov, M. Arslandok, M.C. Danisch, A. Deisting, P. Glässel, J. Kim, S. Klewin, M.L. Knichel, L. Leardini, J. Mercado Pérez, H. Oeschler, A. Ohlson, Y. Pachmayer, F. Reidt, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, M.A. Völkl, D.F. Weiser, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und weitere]
Gesehen am 17.10.2018